2014
DOI: 10.1115/1.4027945
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness Analysis and Control of a Stewart Platform-Based Manipulator With Decoupled Sensor–Actuator Locations for Ultrahigh Accuracy Positioning Under Large External Loads

Abstract: Robot frame compliance has a large negative effect on the global accuracy of the system when large external forces/torques are exerted. This phenomenon is particularly problematic in applications where the robot is required to achieve ultrahigh (micron level) accuracy under very large external loads, e.g., in biomechanical testing and high precision machining. To ensure the positioning accuracy of the robot in these applications, the authors proposed a novel Stewart platform-based manipulator with decoupled se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…An adaptive velocity-based load control algorithm was implemented on a parallel robot (Ding et al, 2011(Ding et al, , 2014) and demonstrated on an ovine FSU. This algorithm builds upon the velocitybased methods of Goertzen and Kawchuk (2009) and improves upon previous implementations of load control (Goertzen and Kawchuk, 2009;Walker and Dickey, 2007;Bell et al, 2013;Bennett and Kelly, 2013), particularly in its ability to test at physiological rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An adaptive velocity-based load control algorithm was implemented on a parallel robot (Ding et al, 2011(Ding et al, , 2014) and demonstrated on an ovine FSU. This algorithm builds upon the velocitybased methods of Goertzen and Kawchuk (2009) and improves upon previous implementations of load control (Goertzen and Kawchuk, 2009;Walker and Dickey, 2007;Bell et al, 2013;Bennett and Kelly, 2013), particularly in its ability to test at physiological rates.…”
Section: Discussionmentioning
confidence: 99%
“…Displacements and rotations of the specimen were directly measured by six linear optical encoders with a resolution of 0:5 μm (B366784180185 LDM54, MicroE Systems, USA) that were positioned independently to the loading frame and load cell. This configuration eliminated system compliance from the measurement of specimen behaviour, as detailed in Ding et al (2011Ding et al ( , 2014. Forces and moments were measured by a six axis load cell (MC3A-6-1000, AMTI, USA) having a maximum axial compressive force capacity of 4450 N and 56.5 N m of axial torque.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have recognized that loading can have a significant effect on a stiffness analysis [19,20], which in turn can affect stability [21] and accuracy [22,23]. It also means that stiffness properties can be controlled in redundantly actuated manipulators [24,25].…”
Section: Introductionmentioning
confidence: 98%
“…The properties of material vary according to the loading order and loading value, that's to say the different loading orders and values can result in the coupling effect [5,6,7]. A novel Stewart platform-based manipulator was analyzed for applications where ultrahigh accurate positioning is required under large external loads by Ding [8]. A multidimensional loading material testing machine was proposed and multidimensional loading and standard tension material tests were established by Guo [9][10][11].…”
Section: Introductionmentioning
confidence: 99%